ANALYSIS OF COMBINED FIXING SYSTEMS FOR STRETCH CEILINGS IN ROOMS WITH COMPLEX ARCHITECTURE - Pogribnyi, Andrii (Global Prosperity, 2023)
Abstract. The article discusses the features of using combined fastening systems for stretch ceilings in rooms with complex architecture. The relevance of the problem is justified in connection with the spread of projects that include arched, domed, multi-level, and curved structures, where traditional installation methods do not provide the necessary accuracy and durability. The current state of research and publications covering both technical and design aspects of the topic is analyzed. Particular attention is paid to the structural and material characteristics of combined profile systems, their zoning by functional areas, the introduction of compensating elements, and the possibilities for integration with engineering networks and decorative elements. A comparative analysis of combined and traditional fastening systems is performed, and the advantages of the former approach in conditions of complex space geometry are determined. A sequence for selecting the optimal technology is proposed, taking into account the structural characteristics of the building, operating conditions, design tasks, and economic feasibility. Recommendations are given for ensuring measurement accuracy, the correct selection of materials and design solutions, as well as a forecast for the development of combined fastening technologies. The results obtained can be used by architects, designers, and installation specialists to improve the efficiency of project implementation in rooms with complex architecture.